Advances on Microwave Ceramic Filters for Wireless Communications (Review Paper) - Stelios Tsitsos (Institute of Advanced Engineering and Science, 2018)
A review of the technological developments on ceramic monoblock filters and duplexers over the years is presented in this work. Early designs based on simulated and measured data are presented along with later designs based on accurate equivalent circuits as well as the use of evolution algorithms for optimal design.